Watch out for sharks! - Arnold, Caroline; Hewett, Richard; Natural History Museum of Los Angeles County (New York : Clarion Books, 1991)
Depicts the world of sharks through text and graphics based on an international touring exhibit about these predators of the sea.
"Focuses on the exhibit Sharks: fact and fantasy, which was organized by the Natural History Museum of Los Angeles County and on view there from June 30, 1990 through September 23, 1990"--P. [3].
Includes bibliographical references (p. 48) and index.
School Library Journal
Kirkus Reviews
6.5
3-6
Keywords: Sharks -- Juvenile literature; Sharks -- Exhibitions -- Juvenile literature; Sharks; Sharks